EXAMINING THE EFFECT OF EMOTIONAL INTELLIGENCE ON LEADERSHIP EFFECTIVENESS AND EMPLOYEE MOTIVATION - Ichwanudin, Wawan (KRIEZ ACADEMY : Journal of development and community service, 2025)
Background Organizations today operate in an increasingly volatile environment characterized by frequent crises, such as natural disasters, cyberattacks, and economic downturns. These disruptions threaten operational stability and long-term viability, emphasizing the need for effective crisis management. Organizational resilience—the ability to adapt, recover, and thrive during and after crises—is essential for sustaining success. Resilience requires a multifaceted approach, integrating proactive planning, adaptive leadership, clear communication, technological innovation, and a supportive organizational culture. This study investigates how crisis management strategies enhance resilience and provides actionable insights for improving preparedness and response. Aims The study aims to explore the role of crisis management strategies in strengthening organizational resilience. Specifically, it identifies critical factors that contribute to resilience, such as leadership, communication, technology, and collaboration. Additionally, it provides practical recommendations for organizations seeking to enhance their crisis preparedness and response capabilities. By addressing these objectives, the study bridges the gap between theory and practice in managing organizational crises. Research Method A mixed-methods approach was employed to provide a comprehensive understanding of the relationship between crisis management and resilience. Quantitative surveys were conducted with 500 professionals across diverse industries to capture trends and assess the effectiveness of crisis management practices. Complementing this, qualitative interviews with 50 leaders and employees, along with three detailed case studies, provided in-depth perspectives on real-world applications. Data analysis included statistical correlations for quantitative findings and thematic evaluations for qualitative insights, ensuring a holistic view of effective crisis management strategies. Results and Conclusion The study identifies six key strategies that enhance organizational resilience. First, proactive planning, including risk assessments and crisis simulations, was found to improve readiness for unexpected events. Second, adaptive leadership, characterized by flexibility, empathy, and vision, played a critical role in guiding teams through crises while maintaining morale. Third, effective communication—both transparent and timely—was essential for fostering trust and collaboration among employees and stakeholders. Fourth, technological integration, such as real-time monitoring systems and digital collaboration tools, enhanced agility and decision-making. Fifth, a resilient organizational culture that promotes trust, innovation, and teamwork helped sustain performance during crises. Lastly, strategic external collaborations with partners and stakeholders provided additional resources and expertise, ensuring a more robust response to complex challenges. These strategies collectively improved recovery times, employee engagement, and stakeholder trust, underscoring the strong link between crisis management and resilience. Contribution This study contributes to the understanding of organizational resilience by integrating diverse crisis management strategies into a cohesive framework. The findings offer practical guidance for organizations to enhance their preparedness, response, and recovery efforts. By applying these insights, organizations can better navigate uncertainty, safeguard stability, and sustain long-term growth, highlighting the strategic importance of crisis management in today’s complex environment.